Architectural Foundations for Serverless Bulk-Update Orchestration in Data-Intensive Applications - Vamsi Praveen Karanam (Journal of Computer Science and Technology Studies, 2025)
This article presents the architectural foundations for serverless bulk-update orchestration in data-intensive applications. The transition from traditional batch processing to serverless models has created new possibilities for scalable data operations while introducing unique challenges for maintaining transactional integrity across distributed systems. The core architectural principles—atomic-update semantics, idempotent function design, state-machine composition, and event-sourcing patterns—provide a framework for reliable data processing at scale. Implementation considerations address long-running transactions in stateless environments, schema drift management, hotspot throttling prevention, and concurrency optimization. Performance characteristics are examined through formal scalability metrics, complexity analysis of parallel workflows, cost elasticity models, and fault tolerance mechanisms. Case studies across multiple domains demonstrate the practical benefits of these architectural approaches, while acknowledging current limitations including execution duration constraints and data locality challenges. Emerging directions point toward specialized programming models, adaptive orchestration systems, and enhanced state management capabilities that will further advance serverless data processing capabilities.